Influence of SASAMBO Cultural Values on Character Building and Civic Learning Management - Muttaqin, Zedi; Susetyarini, Rr Eko; Widodo, Joko (Moestopo International Review on Social, Humanities, and Sciences, 2026)
This study aims to analyze the influence of integrating SASAMBO local cultural values on character education strengthening and the management of Civic Education learning among students at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Mataram. The study used a quantitative survey approach with a sample of 153 students selected through snowball sampling. Data were collected using a 25-item Likert scale questionnaire and analysed using descriptive statistics and multiple regression using SPSS. The results showed that local culture had a significant influence on character building with a contribution of 41.4%, while the influence on PPKn learning management was 9.2%. These findings confirm that the internalisation of the values of mutual cooperation, tolerance, religiosity, and social responsibility effectively strengthens students' attitudes and morals, but improving learning management also requires the support of pedagogical and institutional factors. The implication is that the integration of local wisdom needs to be optimised as the basis for character education and combined with managerial strategies and learning innovations so that the effectiveness of Civic Education in higher education is more comprehensive and sustainable.